Novel method of electrical resistance measurement in structural composite materials for interfacial and dispersion evaluation with nano- and hetero-structures. Issue 1700 (2014) - Park, Joung-Man; Kwon, Dong-Jun; Wang, Zuo-Jia; Byun, Joon-Hyung; Lee, Hyung-Ik; Park, Jong-Kyoo; DeVries, Lawrence K.
ABSTRACT: Interest in development in the use of nanoparticles in structural composites for the improvement of thermal conductivity, mechanical properties and electrical properties has recently stimulated some research efforts. Such improvements require the introduction of functional groups and the proper selection and concentration of the nanoparticles, as well as their uniform dispersion. The identification and verification of uniformity of dispersion is very important in the efficient processing for improved performance. Recently, new methods for studying and evaluating the interfacial properties between the reinforcing fibers and the epoxy matrix, have been developed. Distinct from FE-SEM observation, electrical resistance methods are being developed which can be applied for to measure interfacial shear strength (IFSS) and degree of dispersion. The main principle, on which the electrical resistance measurement is based, is Kirchhoff's laws, which considers conductive materials as electrical circuits. In this research, the self sensing character of the conductive carbon nanotubes (CNT) and conventional carbon reinforcing fibers has been successfully used as a method for evaluating the dispersion of nanoparticles and interfacial adhesion. The electrical resistance in these composites was observed to be dependent on differences in wetting and interfacial adhesion between matrix and fillers. In summary, a correlation was observed between the electrical resistance and dispersion and degree of cure. It is felt that these methods, along with the electro-micromechanical methods, provide valuable tools for investigating the role of interfacial behavior on thermal conductivity, electrical and mechanical properties. Optical observations by FE-SEM of degree of dispersion and interfacial adhesion are consistent with the electrical resistance results. Additionally, it may be possible to use electrical resistance circuit analysis to detect the location of and extent of micro-damage within composite materials.